Study on the bearing resistance of axially compressed L-shaped stainless steel core plate wall based on the stability loss. (15th December 2021) - Shu, Xing-Ping; Wang, Huai-Bing; Li, Yi; Yuan, Zhi-Shen; Li, Ke
Highlights: An innovative stainless steel core plate wall (SSCPW) is introduced. Failure mechanism of L-shaped SSCPW under axial compression is investigated. The effect of parameters on the bearing resistance of L-shaped SSCPW is discussed. The design formulas of stability bearing capacity of L-shaped SSCPW are proposed. Abstract: An innovative wall structure, the stainless steel core plate wall, abbreviated as SSCPW, is composed of two stainless steel plates and orthogonally arranged stainless steel core tubes connecting the plates. In order to investigate the loading process and failure mechanism of the axially compressed L-shaped SSCPW, three references of such specimens were designed for studying the system by both physical experiments and finite element analyses. The results indicate that local buckling will reduce the resistance of the L-shaped SSCPW members remarkably. The finite element models established for the members were validated against the experimental results. The influencing parameters include aspect ratio of the wall, thickness of the plates, size of the core tubes, wall thickness of the core tubes and distribution of the tubes, and the effect of these on the bearing resistance is discussed in detail. The formulas for evaluating the elastic buckling load of the L-shaped SSCPW and the regularized aspect ratio were derived by the eigenvalue buckling analysis. The stability coefficients and corresponding curve were proposed accordingly. Good agreement between the experimental results, those from the finite element analyses and the empirical formulas indicates that the proposed design resistance based on the stability loss is safe and effective for the L-shaped SSCPW.